Effect of SKT Meditation Program on Quality of Life for Persons with Chronic Renal Failure - Chatrung, Chutikarn; Sangkhapong, Somrak; Thanatrakulpanich, Chaicharoen; Janphibunnaratin , Potjaman; Tengtrongdee, Punyaporn; Singhaphan, Thanakorn; Pimporn, Somruthai; Saeton, Tangmo; Sriladee, Wanida (NU Journal of Nursing and Health Sciences, 2023)
This quasi-experimental study with a one-group pretest-posttest design aimed to compare the quality of life of patients with CKD before and after SKT meditation program. The 34 samples were purposefully selected based on the inclusion criteria: 1) be diagnosed with stage 3 or 4 CKD 2) live in the health district of a health promoting hospital in one Tambon, Muang District, Suphanburi Province 3) have a telephone to communicate with the investigator; and 4) be conscious and communicate in Thai. The research instrument included: 1) the SKT Meditation Therapy Program, which included CKD workshops, the three postures of SKT meditation therapy (SKT1, SKT3, and SKT6), and the SKT therapeutic meditation record; and 2) the data collection instruments, which included a demographic data questionnaire and the Kidney Disease Quality of Life - Short Form Version 1.3 (KDQOL-SF TM 1.3) with Cronbach’s alpha coefficient .71-.94. The study was conducted for 8 weeks. The descriptive statistics and paired t-test were applied in this study. The results showed that the majority of the sample was male (52.94%), between 80-89 years old (35.30%), and had two comorbidities (41.20%). Before the trial, the overall quality of life score of the sample was “moderate” ( = 59.32, S.D. = 16.57) After the trial, the overall quality of life average score was “good” ( = 77.03, S.D. = 10.20). The quality of life after the trial was statistically significantly higher than before the trial. (t = 8.43, p = .000) The health care team should encourage people with CKD to do SKT meditation therapy in SKT1, SKT3, and SKT6. This therapy stimulates the body’s circulatory system, which helps bring more blood to the kidneys, slows down kidney degeneration, and improves quality of life over time.